Plant Epigenetics and Epigenomics Methods and Protocols - Spillane, Charles; McKeown, Peter C. (Methods in Molecular Biology, Methods and Protocols, 2014)
Many fundamental discoveries concerning epigenetics and the elucidation of mechanisms of epigenetic regulation have developed from studies performed in plants. In Plant Epigenetics and Epigenomics: Methods and Protocols , leading scientists in the epigenetics field describe comprehensive techniques that have been developed to understand the plant epigenetic landscape.  These include recently developed methods and techniques for analysis of epigenetically regulated traits, such as flowering time, transposon activation, genomic imprinting and genome dosage effects. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoidance of known pitfalls.       Authoritative and practical, Plant Epigenetics and Epigenomics: Methods and Protocols seeks to aid scientists in the further study of plant epigenetic phenomena using advanced contemporary methods